STRATEGI GURU DALAM MENINGKATKAN PRESTASI SISWA DALAM PEMBELAJARAN PAI DI MASA PENDEMI COVID-19 DI SMAI AL MA’ARIF SINGOSARI - Binti Chabibah Fatchiyyah; Nur Hasan; Bahroin Budiya (VICRATINA, 2022)
Learning activities at Smai Al Ma’arif Singosari Malang are carried out using the Whatsapp application, google classroom and other online applications that are monitored directly by the teacher. In addition, it also implements an offline school system, where a teacher will come to teach between one Islamic boarding school and another, because the majority of students at SMAI Al Ma'arif Singosari Malang live in Islamic boarding schools. From the background of the research above, the researcher formulates the problem, how is the learning process carried out at SMAI Al Ma'arif Singosari. the learning process was carried out at SMAI Al Ma'arif Singosari. The process of implementing learning at SMAI Al Ma'arif Singosari during the Covid-19 pandemic. Every learning activity is certainly expected to carry out learning in a structured and planned manner. Likewise, in the process of implementing learning during the Covid-19 pandemic, adapting starting from online and offline learning models which are carried out in two places, namely at home and Islamic boarding schools. For lessons with the Online System will be carried out at home, especially for students who live at home. While offline, it is held face-to-face, where the teacher will come personally to the Islamic boarding school to teach.